Ten things to know about ten cardiovascular disease risk factors - 2022 - Harold E Bays; Anandita Agarwala; Charles German; Priyanka Satish; Adedapo Iluyomade; Ramzi Dudum; Aarti Thakkar; Mahmoud Al Rifai; Anurag Mehta; Aneesha Thobani; Yousif Al-Saiegh; Adam J Nelson; et al. (Elsevier, 2022)
ABSTRACT: The American Society for Preventive Cardiology (ASPC) ''Ten things to know about ten cardiovascular disease risk factors - 2022'' is a summary document regarding cardiovascular disease (CVD) risk factors. This 2022 update provides summary tables of ten things to know about 10 CVD risk factors and builds upon the foundation of prior annual versions of ''Ten things to know about ten cardiovascular disease risk factors" published since 2020. This 2022 version provides the perspective of ASPC members and includes updated sentinel references (i.e., applicable guidelines and select reviews) for each CVD risk factor section. The ten CVD risk factors include unhealthful dietary intake, physical inactivity, dyslipidemia, pre-diabetes/diabetes, high blood pressure, obesity, considerations of select populations (older age, race/ethnicity, and sex differences), thrombosis (with smoking as a potential contributor to thrombosis), kidney dysfunction and genetics/familial hypercholesterolemia. Other CVD risk factors may be relevant, beyond the CVD risk factors discussed here. However, it is the intent of the ASPC ''Ten things to know about ten cardiovascular disease risk factors - 2022" to provide a tabular overview of things to know about ten of the most common CVD risk factors applicable to preventive cardiology and provide ready access to applicable guidelines and sentinel reviews.